Problems of management risks of informative providing of realization of innovations - Ozarko, K.; Chelombytko, V. (Економічний вісник Донбасу, 2022)
The work investigated the problems of risk management of information support for implementing innovations. Under current, highly dynamic operating conditions, any processes (including business processes) are inseparable from risk. It is inherent in all branches of market activity. Risks cannot be ignored. It is advisable to use anticipatory (preventive) measures to prevent them, reduce their level, or compensate depending on the types of risks, circumstances of their occurrence, level, etc. Ensuring the sustainable development of domestic enterprises under the current conditions of instability and crisis in Ukraine is significantly complicated by significant risk factors.
An important condition for effective information provision in implementing innovative projects is the ability to turn uncertainty into risk and its subsequent management. Information support for implementing innovations (implementation of innovative projects) is characterized by a high level of risk. The paper analyzes the risk structure of the stakeholders of the innovative project. The proposed process of step-by-step risk management of the information support of the enterprise's innovative activities. The proposed risk management system of information support for implementing innovations by enterprises consists of applying key (main) functions. A functional approach to the risk management process of information support for implementing innovations will involve the planning and organization of this activity, as well as further control and, in the event of deviation from the plan, regulation (adjustment). For the effective implementation of innovative projects, domestic enterprises need to investigate and manage the risks of information provision of this activity at each stage. Improvement, development of information provision of innovative projects, and formation of the risk management system of this activity will help save time for all participants, increase efficiency and accuracy, and reduce uncertainty. У роботі досліджено проблеми управління ризиками інформаційного забезпечення впровадження інновацій. У сучасних високодинамічних умовах функціонування будь-які процеси (у тому числі бізнес-процеси) невіддільні від ризику. Він притаманний усім галузям ринкової діяльності. Не можна ігнорувати ризики. Доцільно використовувати випереджувальні (попереджувальні) заходи щодо їх запобігання, зниження рівня або компенсації залежно від видів ризиків, обставин їх виникнення, рівня тощо. Забезпечення сталого розвитку вітчизняних підприємств в сучасних умовах нестабільності та кризи в Україні суттєво ускладнено значними факторами ризику.
Важливою умовою ефективного інформаційного забезпечення при реалізації інноваційних проектів є вміння перетворювати невизначеність на ризик і подальше управління ним. Інформаційне забезпечення впровадження інновацій (реалізація інноваційних проектів) характеризується високим рівнем ризику. У статті проаналізовано структуру ризиків стейкхолдерів інноваційного проекту. Запропонований процес поетапного управління ризиками інформаційного забезпечення інноваційної діяльності підприємства. Запропонована система управління ризиками інформаційного забезпечення впровадження інновацій підприємствами складається із застосування ключових (основних) функцій. Функціональний підхід до управління ризиками процесу інформаційного забезпечення впровадження інновацій передбачатиме планування та організацію цієї діяльності, а також подальший контроль і, у разі відхилення від плану, регулювання (коригування). Для ефективної реалізації інноваційних проектів вітчизняним підприємствам необхідно досліджувати та управляти ризиками інформаційного забезпечення цієї діяльності на кожному етапі. Удосконалення, розвиток інформаційного забезпечення інноваційних проектів, формування системи управління ризиками цієї діяльності сприятиме економії часу всіх учасників, підвищенню ефективності та точності, зменшенню невизначеності.